2018
DOI: 10.1007/s00381-018-3848-0
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic third ventriculostomy (ETV) and ventriculoperitoneal shunt (VPS) in non-communicating hydrocephalus (NCH): comparison of outcome profiles in Nigerian children

Abstract: VPS compared to ETV is associated with an earlier milestone and OFC response. ETV is associated with lower rates of sepsis and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…NPH is classically defined as a communicating form of hydrocephalus 37 , 73 - 75 without a fully effective non-invasive treatment. 22 , 76 - 80 However, because of the new hydrodynamic concept of hydrocephalus, 81 , 82 as opposed to the classical dichotomy proposed by Dandy, 82 , 83 the use of endoscopic third ventriculostomy (ETV), which is the golden standard for non-communicating cases, 84 has been reported in selected cases of NPH, as an attempt to restore normal intracranial compliance and pulsatility, normalizing the CSF dynamics. 81 , 82 , 85 - 88 The results showed an effectiveness rate of ETV ranging from 21% to 72%.…”
Section: Idiopathic Normal-pressure Hydrocephalus (Inph)mentioning
confidence: 99%
“…NPH is classically defined as a communicating form of hydrocephalus 37 , 73 - 75 without a fully effective non-invasive treatment. 22 , 76 - 80 However, because of the new hydrodynamic concept of hydrocephalus, 81 , 82 as opposed to the classical dichotomy proposed by Dandy, 82 , 83 the use of endoscopic third ventriculostomy (ETV), which is the golden standard for non-communicating cases, 84 has been reported in selected cases of NPH, as an attempt to restore normal intracranial compliance and pulsatility, normalizing the CSF dynamics. 81 , 82 , 85 - 88 The results showed an effectiveness rate of ETV ranging from 21% to 72%.…”
Section: Idiopathic Normal-pressure Hydrocephalus (Inph)mentioning
confidence: 99%
“…25 Studies abroad, including a Nigerian prospective study by Uche et al, have demonstrated higher complication (9%-15%) and reoperation (20%) rates after CSF shunt insertion than those after ETV (4%-8% and 4%, respectively). 26 In the first multiinstitutional prospective study comparing CSF shunt insertion and ETV, IIHS investigators demonstrated greater success rates with CSF shunt insertion (83% at 12 months, 79% at 24 and 36 months) as opposed to ETV (66% at 12 months, 64% at 24 and 36 months). 3 These comparison studies help with the decision between treatment strategies for permanent CSF diversion but incorporate narrow sets of outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in both meta-analyses may be due to sample size as Jiang included 2017 patients while Saekhu included 1513 besides differences in reported outcomes in both studies. Uche EO 2018 conducted prospective cohort compared between ETV and VP shunt in children with non-communicating hydrocephalus and showed VPS is associated with an earlier milestone and OFC response while ETV is associated with lower rates of sepsis and mortality [13]. Systematic review by Dewan MC 2017 concerned with children with hydrocephalus following posterior fossa tumor resection showed ETV has long-term treatment durability and sooner failure rate but was associated with lower incidence of complications compared to VP shunt [14].…”
Section: Discussionmentioning
confidence: 99%